Junie B., first grader : boss of lunch - Park, Barbara; Brunkus, Denise (New York Scholastic, 2002)
Junie, an outspoken, sometimes exasperating, first grader is thrilled when she is told she can help out in the school cafeteria.
K
"A stepping stone book."
b
K
Keywords: Schools -- Fiction; School lunchrooms, cafeterias, etc. -- Fiction